Research on tetrahedral adaptive mesh grading refinement for intersecting faults - CHEN Yingxian; ZHU Zhe; MA Huiru; FU Jiepeng (Gong-kuang zidonghua, 2024)
Current tetrahedral adaptive mesh refinement techniques have primarily focused on the 3D reconstruction and analysis of simple stratified geological bodies. When applying adaptive mesh refinement to complex geological structures, such as those containing intersecting faults with discontinuous data, excessive refinement can easily lead to compromised mesh structures in the fault zones. To improve the accuracy of tetrahedral mesh models for such complex fault systems, this study proposed a tetrahedral adaptive mesh grading refinement method specifically for intersecting faults. Initially, the refinement range around the fault was adaptively determined based on a fault influence formula. Subdivision formulas were then developed for tetrahedrons and tetrahedral edges to grade both the tetrahedrons and their edges within the refinement range. To address the various scenarios that arose during tetrahedral mesh subdivision, the eight types of subdivisions were unified into three types by upgrading the edge treatments. Finally, new vertices were introduced, and existing vertices were reconnected to tetrahedrons within the refined area, adjusting mesh element sizes to generate a high-quality mesh model. A case study was conducted on a tetrahedral mesh model from an open-pit coal mine in Inner Mongolia. The mesh model was analyzed before and after refinement using a 3D mesh quality evaluation algorithm and FLAC3D simulation software. Results showed that the distortion value of the refined mesh model decreased from 0.3317 to 0.3061, indicating an improvement in mesh quality. Under the same parameters, the unrefined model exhibited a maximum displacement of 1.16 m with a stability coefficient of 1.27, while the refined model showed a maximum displacement of 1.29 m and a stability coefficient of 1.23. The displacement cloud map of the refined model was aligned with the fault, accurately reflecting the fault distribution and its impact on the slope. In contrast, the displacement cloud map of the unrefined model was misaligned with the fault center, demonstrating a less pronounced effect of the fault on the slope.